Implikatur, Praanggapan dan Entailment pada Film Pendek Pak, Buk, Kulo Mantuk - Indraswuri, Fatimah Dwi; Oktaviani, Wulan (STKIP PGRI Ponorogo Press, 2024)
Pragmatics is a branch of linguistics that deals with speech acts. In a communication, it is certain that a conversation will occur. Pragmatics deals with meaning in context with the aim of being able to analyze from various points of view. Pragmatics also bridges the gap between language systems and their use. An utterance must be bound by context. The context referred to here is grammatized and codified so that it cannot be separated from the structure of the language. Implicature means something that is implied in a conversation or dialogue. In addition to implicatures, in the field of pragmatics there are also presuppositions. Presupposition is shared knowledge that is owned by speakers and interlocutors which is the background of a speech act. Entailment is something that logically exists or follows what is emphasized in the utterance. In this article the researcher will analyze whether there are implicatures, presuppositions and entailments in the short film